Effectiveness of a Neck Stretching Intervention on Nurses' Primary Headaches. (March 2015) - Lin, Li-Ying; Wang, Ruey-Hsia
This study examined the effects of a neck stretching exercise intervention on nurses' primary headaches. Using a pretest and posttest two-group design, a total of 60 female staff nurses employed by a medical center in Taiwan were selected by convenience sampling. Participants in the experimental group ( N = 30) practiced neck stretching exercises while experiencing headaches. The participants in the control group ( N = 30) managed their headaches as usual. A structured questionnaire was used to collect data on headache intensity at baseline, and at 30 minutes and 1 hour after intervention. Decrease in headache intensity of the experimental group was significantly larger than that of the control group. Neck stretching exercises is an effective method for treating primary headaches.